2023
DOI: 10.1038/s41698-023-00347-2
|View full text |Cite
|
Sign up to set email alerts
|

Genomic landscape of 891 RET fusions detected across diverse solid tumor types

Abstract: In this study, we report the clinicopathologic and genomic profiles of 891 patients with RET fusion driven advanced solid tumors. All patient samples were tested using a tissue-based DNA hybrid capture next generation sequencing (NGS) assay and a subset of the samples were liquid biopsies tested using a liquid-based hybrid capture NGS assay. RET fusions were found in 523 patients with NSCLC and in 368 patients with other solid tumors. The two tumor types with the highest number of RET fusion were lung adenocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 48 publications
(53 reference statements)
2
12
0
Order By: Relevance
“…With the utilization of next‐generation sequencing (NGS) technology, over 50 distinct fusion partners have been identified, indicating a diverse and varied distribution in their occurrence. This demonstrates a clear long‐tail effect in the incidence distribution of RET fusion events 21 …”
Section: The Biological Basis Of the Ret Genementioning
confidence: 83%
See 1 more Smart Citation
“…With the utilization of next‐generation sequencing (NGS) technology, over 50 distinct fusion partners have been identified, indicating a diverse and varied distribution in their occurrence. This demonstrates a clear long‐tail effect in the incidence distribution of RET fusion events 21 …”
Section: The Biological Basis Of the Ret Genementioning
confidence: 83%
“…This demonstrates a clear long-tail effect in the incidence distribution of RET fusion events. 21 Activating point alterations represent another significant oncogenic mutation associated with inherited diseases such as multiple endocrine neoplasia 2A (MEN2A), multiple endocrine neoplasia 2B (MEN2B), and familial medullary thyroid carcinomas. These mutations are distributed across exons 7 to 16, predominantly occurring in the cysteine-rich domain and tyrosine kinase domains.…”
Section: Ret Gene Alterations and Their Mechanism Of Carcinogenesismentioning
confidence: 99%
“…A retrospective multi-center study has recently investigated clinic-biological features and treatment outcomes of patients with any-stage RET + NSCLC from 31 centers, 30 European and one from Argentina. The most frequent fusion partner was KIF5B followed by CCDC6; no cases were detected with ANK3::RET fusion ( 34 ). RET translocations/fusion genes are predominantly reported in papillary thyroid carcinoma and NSCLC, less in other solid tumors, such as colorectal carcinoma, salivary gland carcinoma, serous ovarian carcinoma, pancreatic and breast carcinoma, in global multicenter networks and reviews; ANK3::RET fusion was seen only in a papillary thyroid cancer ( 12 , 17 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent fusion partner was KIF5B followed by CCDC6; no cases were detected with ANK3::RET fusion ( 34 ). RET translocations/fusion genes are predominantly reported in papillary thyroid carcinoma and NSCLC, less in other solid tumors, such as colorectal carcinoma, salivary gland carcinoma, serous ovarian carcinoma, pancreatic and breast carcinoma, in global multicenter networks and reviews; ANK3::RET fusion was seen only in a papillary thyroid cancer ( 12 , 17 , 34 , 35 ). The study of Parimi et al, reported the clinicopathologic and genomic landscape of a large cohort of RET fusion positive solid tumors (523 patients with NSCLC and 368 with other solid tumors), including the discovery of 61 novel fusions, detected by a DNA tissue-based NGS assay; no case of ANK3::RET rearrangement was detected in all African, Central and South American, East Asian, and South Asian patients ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, each tumor type in the experimental arm would have corresponding control patients, and the trial would be powered for this comparison. In reality, the number of patients with a specific tumor type in the trial is too small for this to be feasible, especially when the overall prevalence of genetic alterations, such as RET or NTRK fusions, 42 , 43 is already low. If patients with an alteration-positive tumor have improved prognoses versus those who are alteration-negative, the apparent increased efficacy seen in tumor-agnostic trials could be partly or wholly due to the prognostic effect of the alteration (ie, confounding) and not the treatment.…”
Section: Discussionmentioning
confidence: 99%